EXAMINATION OF HIGH SCHOOL STUDENT NATIONAL ATHLETES' SELF-ESTEEM IN DECISION MAKING AND DECISION MAKING STYLES - Vural, Mustafa; Özdemir, Adem; Özdemir, Harun; Çoruh, Yaşar; Peker, Alper Tunga; Zengin, Serkan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
Research was carried out to determine self-esteem in decision making and decision-making styles of high school student national athletes in Wrestling, Boxing, Karate, Taekwondo and Judo branches in terms of branch and year of doing sports variables. In the research, the descriptive survey method which aimed to reveal the current situation was used. A total of 135 students engaging in fighting sports and studying in different high schools in Erzurum province, participated in the study. In the research, Melbourne Decision Making Questionnaire consisting of two parts, developed by Mann et al. (1998) and adapted to Turkish by Deniz (2004) was used as the data collection tool. For data analysis, the Mann-Whitney U test was used for paired comparisons and Kruskal-Wallis Variance Analysis was used for multiple comparisons. The significance level in the research, α=0.05 was selected. As a result of the research, it was observed that panic decision making and postponer decision making styles which were sub-dimensions of the scale of decision-making styles, differentiated significantly in terms of athletes engaging in taekwondo branch. It was concluded that the level of self-esteem in decision making differentiated significantly in judo branch. When levels of self-esteem in decision making were examined, it was concluded that self-esteem levels of those engaging in sports for 1 year and less in decision-making decision differentiated significantly according to the year of doing sports and the sub-dimensions of decision-making style scale did not differ differentiated significantly.